Resonant frequency training in elite sport: A case study example. Issue 3 (2nd September 2017) - Gross, Mike J.; Hall, Ross; Bringer, Joy D.; Cook, Christian J.; Kilduff, Liam P.; Shearer, David A.
ABSTRACT: Resonant frequency training (RFT) is a heart rate variability (HRV) biofeedback technique where participants learn bespoke breathing patterns to inhibit autonomic nervous system changes resulting from stress. To demonstrate RFT in sport, we present an intervention case study with an elite female shooter that enabled her to perform optimally, even after missed shots or unexpected interruptions (e.g., target malfunction). This case study represents a data-driven intervention using biofeedback equipment, however we provide suggestions for low-cost and free methods to widen the use of HRV biofeedback in sport.